REVITALISASI PENGELOLAAN MANGROVE MELALUI PERAN PEMERINTAH DALAM KONSERVASI WILAYAH PESISIR DI KABUPATEN ACEH JAYA - Dewi Fithria; Rahmat Hidayat (Universitas Teuku Umar, 2018)
Mangroves act as a filter to reduce the adverse effects of major environmental changes, and as a food source for marine life (Beach) and terrestrial biota. The Tsunami disaster of 2004 have resulted in changes in landforms such as mangrove forests. The damage of mangrove forests and then aggravated it again with pressure and increase the number of resulted in any change land use and natural resource utilization. Mangrove management, should involve all components of the stakeholders which includes the role of Government, local institutions and communities. The purpose of this research was to assess the management of mangroves in the coastal area conservation efforts are integrated through the role of local governments in terms of planning, utilization, control, maintenance, surveillance, and law enforcement in Aceh Jaya Regency. This research includes the types of descriptive research with qualitative approach by describing the strategic role of pemerintahdaerah in the management of mangrove in the Aceh Jaya Regency. Based on the results of the study can be obtained that a summary of the factors facing the Government in the management of mangrove areas include factors financing became a major factor in the realization of program management of mangrove areas, the occurrence of farmed land expansion (neuheun), expansion of the area of the settlements, the lack of human resources so as to affect the economic conditions of the community. System management of mangrove area should preferably be done through a bottom up approach and done in sitematis starts from perencenaan stage, utilization, control, maintenance, supervision and law enforcement. Key words: the role of Government, revitalizing, mangrove management